Unresectable Pancreatic Ductal Adenocarcinoma in the Remnant Pancreas Diagnosed during Every-6-Month Surveillance after Resection of Branch Duct Intraductal Papillary Mucinous Neoplasm: A Case Report - Tamura, Koji; Ohtsuka, Takao; Ideno, Noboru; Aso, Teppei; Kono, Hiroshi; Nagayoshi, Yousuke; Shindo, Koji; Ushijima, Yasuhiro; Ueda, Junji; Takahata, Shunichi; Ito, Tetsuhide; Oda, Yoshinao; et al. (JOP. Journal of the Pancreas, 2013)
Context There are few studies regarding the surveillance period and interval of resected or observed branch duct intraductal papillary mucinous neoplasms (IPMNs) of the pancreas in terms of early detection of concomitant pancreatic ductal adenocarcinoma. Despite a strict surveillance protocol, some patients are diagnosed with metastatic distinct ductal adenocarcinoma after resection of IPMN. Case report We herein report a patient with unresectable pancreatic ductal adenocarcinoma that developed in the remnant pancreas 18 months after resection of branch duct IPMN. Although the patient was surveyed every 6 months after the operation and imaging studies at 6 and 12 months postoperatively demonstrated no evidence of recurrence, invasive ductal adenocarcinoma with liver metastasis appeared 18 months after the operation. The patient subsequently underwent chemotherapy; however, he died 9 months after the diagnosis of metachronous pancreatic ductal adenocarcinoma. Conclusions In some patients with branch duct IPMNs, 6-month surveillance seems to be insufficient to detect resectable concomitant pancreatic ductal adenocarcinoma. Therefore, identification of high-risk patients who require surveillance at shorter intervals is urgently needed. Image: Peroral pancreatoscopy reveals a fish egg-like appearance.